Events Occurring in the Axotomized Facial Nucleus - Kazuyuki Nakajima; Takashi Ishijima (Cells, 2022)
Transection of the rat facial nerve leads to a variety of alterations not only in motoneurons, but also in glial cells and inhibitory neurons in the ipsilateral facial nucleus. In injured motoneurons, the levels of energy metabolism-related molecules are elevated, while those of neurofunction-related molecules are decreased. In tandem with these motoneuron changes, microglia are activated and start to proliferate around injured motoneurons, and astrocytes become activated for a long period without mitosis. Inhibitory GABAergic neurons reduce the levels of neurofunction-related molecules. These facts indicate that injured motoneurons somehow closely interact with glial cells and inhibitory neurons. At the same time, these events allow us to predict the occurrence of tissue remodeling in the axotomized facial nucleus. This review summarizes the events occurring in the axotomized facial nucleus and the cellular and molecular mechanisms associated with each event.